PERNIKAHAN LINTAS AGAMA DI INDONESIA DALAM PRESPEKTIF HADITS - Ananda, Riyan Azrul; Anjarwati, Yuli Febi; Sa’diyah, Nurul Halimatus (Al-Bayan: Journal of Hadith Studies, 2023)
Interfaith marriage is an inseparable characteristic of Indonesian culture, which is steeped in pluralism. The use of state law and customary law by society can give rise to legal pluralism. Legal pluralism is a global phenomenon encompassing various areas of human life, including law, politics, and economics. Legitimate pluralism is an inevitability that must be recognized. Within a legitimate pluralistic structure, society is faced with various legitimate decisions: standard regulations, explicit regulations, and state regulations. Interfaith relationships tend to give rise to spiritual issues and conflict due to the many differences in ways of thinking, perspectives, activities, and daily tendencies, many of which stem from real differences between the two. Consequently, interfaith marriage must be explained from a legal perspective. Being a Muslim is one of the requirements for a valid marriage in Islam. Based on this foundation, the author deems it important to focus on the truth of this event within the strict principles adopted in Indonesia. The purpose of this paper is to explain the logical consequences of interfaith marriage and the interpretation of Islamic law based on the hadith regarding interfaith marriage.